2004
DOI: 10.2174/1568008043340071
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Role in Experimental Arthritis

Abstract: Our perception of the function of the pineal gland and its hormone melatonin has attained a new dimension during the last decade. Through melatonin, the pineal becomes a principal organ present in vertebrates involved in the control of rhythmic adaptations to daily and seasonal cycles. Melatonin is synthesized and secreted during the dark period of the light/dark cycle. The rhythmic nocturnal melatonin secretion is directly generated by the circadian clock and is entrained to a 24-hour period by the light-dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This dose was 10 times higher than that needed to attain physiological circulating melatonin levels in pinealectomized rats. 17 Nocturnal water consumption did not differ among the experimental groups.…”
Section: Animals and Experimental Designmentioning
confidence: 82%
“…This dose was 10 times higher than that needed to attain physiological circulating melatonin levels in pinealectomized rats. 17 Nocturnal water consumption did not differ among the experimental groups.…”
Section: Animals and Experimental Designmentioning
confidence: 82%
“…Maestroni and colleagues reported that melatonin has been found to be present in synovial fluid from rheumatoid arthritis (RA) patients (79.8 ± 38.9 pg/mL) as well as healthy subjects (data not shown) . A high melatonin dose (30 μ g/mL of drinking water) caused a 50‐ to 60‐fold increase in plasma melatonin, which led to enhancement of the immune response in the experimental inflammatory arthritic rats . Synovial macrophages have high‐affinity binding sites for melatonin in RA patients, which may be a potent reason of immune‐enhancing phenomenon by exogenous melatonin .…”
Section: Discussionmentioning
confidence: 99%
“…Synovial macrophages have high‐affinity binding sites for melatonin in RA patients, which may be a potent reason of immune‐enhancing phenomenon by exogenous melatonin . It has been frequently reported the results that indicate the detrimental effect of melatonin on RA pathogenesis , whereas the previous study regarding its effect on OA has been little investigated. Moreover, a direct correlation between blood levels of melatonin and its intracellular concentrations may be erroneous, although melatonin's efficacy in vivo is also often based on the low levels (10–200 pg/mL) of melatonin in the blood .…”
Section: Discussionmentioning
confidence: 99%
“…Since rats drank about 20 mL/day with 90–95% of this total daily water taken up during the dark period, the melatonin dosage used provided approximately 60 μg melatonin/day. This dose was 10 timed higher than that needed to obtain physiological circulating melatonin levels in pinealectomized rats (Cardinali et al, 2004). Nocturnal water consumption did not differ among the experimental groups.…”
Section: Methodsmentioning
confidence: 99%